2021
DOI: 10.1007/s10943-021-01470-9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Spirituality and Hopelessness Among Cancer Patients in Turkey

Abstract: The aim of this study was to determine the relationship between spirituality and hopelessness in cancer patients. The study used a cross-sectional and correlational design and included 650 cancer patients. The data were collected using a patient information form, the Spiritual Orientation Scale, and the Beck Hopelessness Scale. The data were analyzed by MANOVA and linear regression analysis. Cancer patients had high levels of spirituality (89.74 ± 32.79) and low levels of hopelessness (6.50 ± 5.61). A statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Finally, it was revealed that the scores obtained by the participants from the spiritual well-being differed according to marital status, educational level, and monthly income level, and the spiritual well-being of individuals who were married, individuals with high education levels, and individuals with higher monthly incomes was at higher levels. In their study, Tasan and Citlik Saritas (2022) found that participants who were married and whose incomes were equal to their expenses exhibited a higher spiritual tendency. In their study on elderly individuals, So Nam and Sang Bok (2013) revealed that individuals with good economic status had higher levels of spiritual well-being.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, it was revealed that the scores obtained by the participants from the spiritual well-being differed according to marital status, educational level, and monthly income level, and the spiritual well-being of individuals who were married, individuals with high education levels, and individuals with higher monthly incomes was at higher levels. In their study, Tasan and Citlik Saritas (2022) found that participants who were married and whose incomes were equal to their expenses exhibited a higher spiritual tendency. In their study on elderly individuals, So Nam and Sang Bok (2013) revealed that individuals with good economic status had higher levels of spiritual well-being.…”
Section: Discussionmentioning
confidence: 96%
“…With higher spiritual beliefs, in turn, more pronounced coping resources emerge for patients. At the same time, there are opposite findings stating that spirituality is lower than expected among people with lower incomes [45].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a correlation between faith and education. Pahlevan Sharif and Ong [51] as well as Tasan and Citlik Saritas [45] argue that a higher level of education is associated with a decline in spirituality. People with a higher education are more interested in rational explanations and rely less on abstract explanations from spirituality and religion.…”
Section: Discussionmentioning
confidence: 99%
“…The heightened importance of spirituality results from patients' attempts to redefine the meaning of life, which alters after the diagnosis (Ferrel et al, 2003). Numerous studies have shown that cancer patients demonstrate high levels of spirituality (Al-Natour et al, 2017;Gudenkauf et al, 2019;Tasan and Citlik Saritas, 2022). They focus on it at every stage of the disease -from diagnosis to the end-of-life stage or remission (Mercier et al, 2023).…”
Section: Introductionmentioning
confidence: 99%